Integrated Slope Safety Factor Analysis Using Geotechnical Bishop Method and Resistivity Method for Calculating Landslides Probabilities in Imogiri area, Special Region of Yogyakarta - Fahmi, Burhanuddin; Yatini, Yatini (JPSE (Journal of Physical Science and Engineering), 2024)
Landslides potential analysis is very serious issue in disaster mitigation processes. The risk of landslide potential in a slope can be assessed through the calculation of Slope Safety Factors, involving data on soil physical properties, soil mechanics (geotechnical properties), and slope geometry. Research was conducted using a combination of resistivity and Bishop geotechnical methods. The geoelectric method was employed to determine the lithology of landslide materials and the geometry of the sliding plane. The Bishop geotechnical method was used to calculate the slope safety factor based on geoelectric data, soil mechanics data, and rock mechanics data obtained in the study area. A total of 2 geoelectric measurement profiles, each 120-150 meters long, were taken in the Imogiri region of Yogyakarta. The research results indicate that the sliding plane is located at a depth of 10 meters with clay lithology. The calculated slope safety factor using the Bishop method was performed under two conditions: saturated and unsaturated. The saturated slope safety factor has a low value, less than 1.07, while the unsaturated condition yields a higher value, greater than 1.25.